The Keys to Connectivity: The District of Columbia's Innovative Approach to Unlocking Low-Stress Bicycle Networks. Issue 36 (December 2018) - Semler, Conor; Sanders, Meredyth; Buck, Darren; Dock, Stephanie; Cesme, Burak; Wang, Shi
Washington, D.C. (the District) has led the way in the adoption of state-of-the-art bicycle facilities and the innovative application of bicycle level of traffic stress (LTS) mapping for the District. Although the District's LTS network map provides insight into bicycle network accessibility at the street level, the District needs a data-driven mechanism for identifying and prioritizing future investments to improve cycling at the system level. As part of its ongoing District Mobility Project, District Department of Transportation (DDOT) applied a geographic information system (GIS)-based network analysis to its bicycle LTS map to quantify network connectivity on low-stress District streets. This analysis was used to develop a bicycle network accessibility rating for District neighborhoods. The results revealed that though DDOT has invested in a range of innovative projects to improve accessibility in the District, only 27% of the overall network has been connected. By taking the analysis a step further and identifying the bottom 10% of accessible census blocks, DDOT both confirmed existing perceptions about the presence of disconnected low-stress "islands" in the District, and identified key gaps in the overall bicycle network. Using this information, DDOT is able to prioritize future bicycle infrastructure investments, while possessing a data-driven mechanism for assessing and communicating the accessibility benefits offered by individual investments. In addition, the methodology for developing the network accessibility rating provides a proof-of-concept for other jurisdictions looking to maximize the utility of their own LTS network maps.